Economic Coercion and Grey Zone Competition: Reassessing the China-Australia case - McDonagh, Naoise; Bachmann, Sascha-Dominik Dov (Pacific Affairs, 2025)
Economic coercion is recognized as a major policy challenge for global leaders. The case of Beijing's use of economic coercion against Australia (2020-2024) in response to bilateral tensions holds important insights. Research shows that China's coercion efforts failed in two ways: the total costs to Australia's economy were smaller than expected, and Canberra did not change pre-existing policies that triggered the coercion. Failure in this case is attributed to the ability of markets to adjust. Building on this research, we argue that while markets adapted relatively well in the Australia-China case, coercion still produced significant and concentrated subnational costs that differentially impacted Australian state economies. This resulted in political pressure and destabilization effects on Australian federal politics, influencing the provision of concessions favourable to Beijing during bilateral negotiations to restore trade relations. Informed by a novel geoeconomic and hybrid warfare framework, this article therefore offers new insights on the political effects of economic coercion in democracies. Our findings suggest that weaponization of trade can serve as an effective geoeconomic strategy for grey zone/hybrid warfare.
Keywords: Economic Coercion; Economic Security; Geoeconomics; Hybrid Warfare; International Trade